EVALUASI PROGRAM MA'HAD AL -JAMI’AH TERHADAP PENGUATAN LITERASI AL-QUR’AN DAN KECERDASAN EMOSIONAL MAHASISWA UIN PALOPO - Nurzykila Nurzykila; Helmi Kamal; Sudirman Sudirman (Jurnal Manajemen Pendidikan, 2026)
The phenomenon shows that some students do not have the ability to read the Qur'an according to the rules of tajweed and are not able to internalize the values of the Qur'an in controlling emotions and academic behavior. This condition is influenced by the heterogeneity of initial abilities, the limitation of the duration of coaching, and the implementation of the Ma'had Al-Jami'ah Program which runs in parallel with lectures. This situation requires a comprehensive evaluation to assess the effectiveness of the program in strengthening Qur'an literacy and students' emotional intelligence. A mixed methods approach with a concurrent embedded design is used, with qualitative data as the main data and quantitative data as support. The evaluation was carried out using the CIPP (Context, Input, Process, and Product) model to assess the relevance of policies, resource readiness, implementation dynamics, and overall program outcomes. The results show that the program is conceptually aligned with the needs of students and the vision of Islamic education. The implementation of the program is able to improve basic tahsin skills, worship habits, discipline, and emotional calm. However, the achievement of Qur'an literacy is not evenly distributed, especially in the aspect of fluent reading and understanding of the meaning of verses, due to differences in initial abilities and limited coaching time. The affective and spiritual aspects show stronger achievements than the cognitive aspects.